Effect of Baduanjin exercise on primary osteoporosis: study protocol for randomized controlled trial - Chuanrui Sun; Ming Chen; Xiaoyang Wang; Baoyu Qi; He Yin; Yingxia Ji; Na Yuan; Shangquan Wang; Liguo Zhu; Xu Wei (BMC, 2023)
Abstract Background Lack of exercise is often a major cause of chronic disease. Osteoporosis (OP) is a chronic disease with multifactorial co-morbidity. Baduanjin (BDJ) exercise may be a powerful tool for modifying risk factors. The aim is to provide more evidence about the effectiveness of BDJ exercise in improving pain and balance ability in patients with OP. Methods In the prospective randomized controlled trial, 160 participants will be recruited and randomized to the treatment group (BDJ exercise combined with Calcium carbonate and D3) or the control group (Calcium carbonate and D3) at 1:1 ratio. Participants in the treatment group will receive 24-week BDJ exercise for 30-60 min, 3 times a week, along with Calcium carbonate and D3 at each day, while participants in the control group will receive Calcium carbonate and D3 only. All outcome indicators will be measured at baseline, after the 6th month of treatment and 6th month after the end of treatment. The primary outcomes include pain and balance ability, as measured by the visual analogue scale (VAS) and Berg balance scale (BBS). The secondary outcomes will primarily include bone mineral density (BMD), laboratory tests (including P1NP, β-CTX, MSTN, FDF-23, NPY), the timed "up and go" (TUG) test, the morse fall scale (MFS), the five-times sit-to-stand test (FTSST). Discussion The study will hopefully confirm that BDJ exercise, as a non-drug intervention, should be recommended for patients with OP to prevent bone loss, falls and fractures. Trial registration International standard randomized controlled trial number (ISRCTN) registry: ISRCTN76945140 registered on 07/06/2022.